Dual-Task Supervised Learning for Distributed Spectrum Monitoring Applications - Shatov, Victor; Shanin, Nikita; Veihelmann, Christian Tobias; Perner, Bastian; Franchi, Norman; Lübke, Maximilian (EuCNC & 6G Summit, 2025)

Enhanced 5G Sidelink Ranging Based on Carrier Aggregation - Rasp, Franziska; Eberlein, Ernst; Perner, Bastian; Roth-Mandutz, Elke; Hipp, Susanne (2023 13th International Conference on Indoor Positioning and Indoor Navigation (IPIN), 2023)
Radio access network based positioning and ranging technologies become more and more important for autonomous driving. Positioning on the 5G Sidelink (SL) is discussed in Release 18 (2022-2024) of the Third Generation Partnership Project. For accurate timing-based ranging, a high temporal and spatial resolution is fundamental. The bandwidth for 5G SL positioning is limited due to sharing the existing SL resources with communication. Therefore, we send the positioning reference signal on two separate Component Carriers, i.e. we use a fragmented spectrum. We introduce a two step algorithm for estimating the time of arrival using the inflection point method. We proved a fragmented spectrum can achieve the same accuracy as a continuous spectrum.<br
Keywords: Correlation; Upper bound; 5G mobile communication; Indoor navigation; Bandwidth; Position measurement; Distance measurement; Sidelink; V2X; 5G mobile communication; Distance measurement; Ranging; Positioning

LSTM-DNN-Based Joint Wireless Signal Waveform Classification and Blind Transmitter Localization - Shatov, Victor; Shanin, Nikita; Perner, Bastian; Su, Yanpeng; Franchi, Norman; Lübke, Maximilian (International Symposium on Wireless Communication Systems (ISWCS), 2024)

Opportunistic 5G Spectrum Usage for Nomadic Ad-Hoc Emergency Communication - Horbach, Konrad; Perner, Bastian; Rehmann, Willi; Kretschmer, Mathias; Lübke, Maximilian; Rademacher, Michael; Franchi, Norman (2024 IEEE Future Networks World Forum (FNWF), 2024)

Optimized Measurement Location Planning for Interpolation-based Radio Environment Maps - Perner, Bastian; Franchi, Norman; Lübke, Maximilian (EUSIPCO, 2025)